2003
DOI: 10.1124/dmd.31.5.559
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Regulation of Rat Organic Anion Transporters

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:Messenger RNA levels of rat organic anion transporter 1 (Oat1; Slc22a6) and Oat2 (Slc22a7) in kidney and Oat3 (Slc22a8) in liver are gender-predominant. Oat1 and Oat3 are male-predominant, whereas Oat2 is female-predominant. Gonadectomized and hypophysectomized (HX) rats were studied to determine whether sex steroids and/or growth hormone (GH) are responsible for these gender-divergent patterns. GH was administered to HX rats by two dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
54
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 23 publications
6
54
1
Order By: Relevance
“…In addition, in contrast to renal rOat2, testosterone increased rOat3 mRNA levels in the liver of male rats [124]. Consistent with this observation, gonadectomy reduced hepatic rOat3 mRNA levels in males [125]. In contrast, gonadectomy did not affect rOat3 mRNA levels in female livers [125].…”
Section: Gender and Specific Sex Hormonessupporting
confidence: 69%
See 4 more Smart Citations
“…In addition, in contrast to renal rOat2, testosterone increased rOat3 mRNA levels in the liver of male rats [124]. Consistent with this observation, gonadectomy reduced hepatic rOat3 mRNA levels in males [125]. In contrast, gonadectomy did not affect rOat3 mRNA levels in female livers [125].…”
Section: Gender and Specific Sex Hormonessupporting
confidence: 69%
“…Consistent with these findings, administration of estradiol or progesterone to castrated or noncastrated male rats weakly stimulated renal rOat2 mRNA and protein expression [126,127]. In addition, it has been shown that the growth hormone secretion pattern is an important determinant of rOat2 message expression [125]. In particular, continuous growth hormone secretion, as is seen only in females, appears to be important for rOat2 renal expression.…”
Section: Gender and Specific Sex Hormonessupporting
confidence: 53%
See 3 more Smart Citations